Development of a Hydrogen Fuel Cell Hybrid Urban Air Mobility System Model Using a Hydrogen Metal Hydride Tank - Sanghyun Yun; Seok Yeon Im; Jaeyoung Han (Energies)
Hydrogen fuel cell-based UAM (urban air mobility) systems are gaining significant attention due to their advantages of higher energy density and longer flight durations compared to conventional battery-based UAM systems. To further improve the flight times of current UAM systems, various hydrogen storage methods, such as liquid hydrogen and hydrogen metal hydrides, are being utilized. Among these, hydrogen metal hydrides offer the advantage of high safety, as they do not require the additional technologies needed for high-pressure gaseous hydrogen storage or the maintenance of cryogenic temperatures for liquid hydrogen. Furthermore, because of the relatively slower dynamic response of hydrogen fuel cell systems compared to batteries, they are often integrated into hybrid configurations with batteries, necessitating an efficient power management system. In this study, a UAM system was developed by integrating a hydrogen fuel cell system with hydrogen metal hydrides and batteries in a hybrid configuration. Additionally, a state machine control approach was applied to a distribution valve for the endothermic reaction required for hydrogen desorption from the hydrogen metal hydrides. This design utilized waste heat generated by the fuel cell stack to facilitate hydrogen release. Furthermore, a fuzzy logic control-based power management system was implemented to ensure efficient power distribution during flight. The results show that approximately 43% of the waste heat generated by the stack was recovered through the tank system.